Ultrasonic concentration measurement of citrus pectin aqueous solutions using PC and PLS regression - Meng, Ruifeng; Zhong, Jianjun; Zhang, Lifen; Ye, Xingqian; Liu, Donghong (International Journal of Agricultural and Biological Engineering, 2012)
Meng Ruifeng, Zhong Jianjun, Zhang Lifen, Ye Xingqian, Liu Donghong* (School of Biosystems Engineering and Food Science, Zhejiang University, Hangzhou 310058, China) Abstract: This work demonstrated the use of multivariate statistical techniques called principal component (PC) and partial least squares (PLS) to extract the acoustic features of citrus pectin water solution. The concentration of citrus pectin water solution was predicted by PC and PLS regression method using the spectra of ultrasound pulse echoes travelling through mixtures. The values of root mean square error of validation (RMSEV) were 0.0675 g/100 g and 0.0662 g/100 g for PC and PLS regression model, respectively. Since the response variable was taken into account, PLS regression model was more accurate than PC regression model. Also, a method for temperature compensation was proposed to correct the impact of temperature variation on analyzed data. The proposed methods for pectin concentration measurement are easily adaptable to similar applications using existing hardware. Keywords: Partial Least Square Regression, Principal Component Regression, concentration measurement, acoustic velocity DOI: 10.3965/j.ijabe.20120502.010 Citation: Meng R F, Zhong J J, Zhang L F, Ye X Q, Liu D H. Ultrasonic concentration measurement of citrus pectin aqueous solutions using PC and PLS regression. Int J Agric & Biol Eng, 2012; 5(2): 76